2009
DOI: 10.1038/cdd.2009.105
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNAs as regulators of death receptors signaling

Abstract: Death receptors, belonging to the TNF receptor superfamily, induce apoptosis through two different pathways, one involving the effector caspases directly (type I cells or mitochondria-independent death), the other one amplifying the death signal through the mitochondrial pathway (type II cells or mitochondria-dependent death). MicroRNAs (miRNAs) are a class of small noncoding RNAs that regulate the stability or translational efficiency of targeted messenger RNAs. MiRNAs are involved in many cellular processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 50 publications
1
69
0
Order By: Relevance
“…MiRNAs are a class of non-coding RNAs that regulate post-transcriptional gene expressions and silence target mRNAs. MiRNAs have been established to act as anti-apoptotic or pro-apoptotic regulators by targeting different mRNAs involved in the apoptotic pathways, especially BCL-2 family proteins (Garofalo et al, 2010;Chen et al, 2014). For example, miR-15/16 targets the antiapoptotic factor (Bcl-2) and the loss or reduced expression of the tumor suppressor of miR-15/16 may elucidate the elevation of Bcl-2 level in some tumors (Cimmino et al, 2005;Allegra et al, 2014).…”
Section: Role Of Apoptosis In Cancermentioning
confidence: 99%
“…MiRNAs are a class of non-coding RNAs that regulate post-transcriptional gene expressions and silence target mRNAs. MiRNAs have been established to act as anti-apoptotic or pro-apoptotic regulators by targeting different mRNAs involved in the apoptotic pathways, especially BCL-2 family proteins (Garofalo et al, 2010;Chen et al, 2014). For example, miR-15/16 targets the antiapoptotic factor (Bcl-2) and the loss or reduced expression of the tumor suppressor of miR-15/16 may elucidate the elevation of Bcl-2 level in some tumors (Cimmino et al, 2005;Allegra et al, 2014).…”
Section: Role Of Apoptosis In Cancermentioning
confidence: 99%
“…9 Among them, the microRNA-34 family mimics p53 biological effects by inducing cell cycle arrest and apoptosis in response to DNA damage. 10,11 Here we studied epithelial cell apoptosis, TP53 and miR-34a expression in skin and gut biopsies in non-transplanted FA patients, and FA patients with aGVHD of different grades.…”
Section: Introductionmentioning
confidence: 99%
“…While early reports indicated that miRs were sensitive markers of toxicity, and might have predictive and diagnostic value in the treatment of APAP (2,15), there have been a few studies that attempted to understand how miR alterations affect Editorial Noncoding RNAs as therapeutics for acetaminophen-induced liver injury APAP-induced liver injury. While it has been established that miRs control a number of cellular functions, the specific functions controlled by different miRs are largely still under investigation (16). Antagonism of miRs has therapeutic potential as they are targetable in a highly specific fashion, and their degradation can have profound effects on transcription of specific genes without affecting the genome.…”
Section: Micro-rnas (Mirs) In Acetaminophen-induced Liver Injurymentioning
confidence: 99%